Pengaruh Paket Teknologi terhadap Produksi Beberapa Varietas Jagung Hibrida - Suparwoto Suparwoto; Joni Karman; Waluyo Waluyo; Atekan Atekan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Suparwoto S, Karman J, Waluyo W, Atekan A. 2020. Effect of technology packages on productionsome varieties of hybrid corn. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The corn production achieved is not sufficient for domestic needs. So efforts to increase corn production continue to be carried out, among others, by using hybrid corn varieties. The objective of the study was to obtain high yielding hybrid maize varieties in accordance with the technology package applied in dry land. The study was carried out in North Indralaya District, Ogan Ilir Regency, South Sumatra Province with an area of 2 ha from April to September 2018 with dry land agro-ecosystems. The study was arranged with a split plot design where as the main plot, namely the recommended technology package and farmer pattern package and as a sub-plot, namely hybrid maize varieties Bima 10, Bima 20, Pioneer 21 and Nasa 29 where three farmers were replicated. The data obtained were tabulated and analyzed by means of the F test, if significantly different, followed by Duncan's test at 5% level using the SPSS program. The results showed that the treatment of the recommended technology package had a significant effect on the farmer pattern technology package of the tested varieties on plant height, ear length without husks and dry shell production per hectare except for ear diameter without cob, wet weight per 5 ear and dry shell weight per 5. cob. The Pioner 21 variety which is supported by the recommended technology package gives the highest production, namely 6.90 tonnes of dry shelled/ha.